Pledges of commitment and cooperation in partnerships - Lachlan Deer; Ralph-C. Bayer (Games, 2016)
We use experimental methods to investigate whether pledges of commitment can improve cooperation in endogenously-formed partnerships facing a social dilemma. Treatments vary in terms of the individual's: (1) opportunity to commit to their partner; (2) the cost of dissolving committed partnerships; and (3) the distribution of these dissolution costs between partners. Our findings show that pledges of commitment alone can increase cooperation and welfare in committed partnerships. The introduction of relatively large and equally split costs yields similar gains. In contrast, when costs to dissolve committed partnerships fall solely on the individual choosing to break up, pledges of commitment fail to improve cooperation and welfare.
Keywords: C92; D03; D83; H41; 330; commitment; cooperation; endogenous group formation; experiment